2013
DOI: 10.1007/978-3-642-37382-4_1
|View full text |Cite
|
Sign up to set email alerts
|

Learning with Configurable Operators and RL-Based Heuristics

Abstract: Abstract. In this paper, we push forward the idea of machine learning systems for which the operators can be modified and finetuned for each problem. This allows us to propose a learning paradigm where users can write (or adapt) their operators, according to the problem, data representation and the way the information should be navigated. To achieve this goal, data instances, background knowledge, rules, programs and operators are all written in the same functional language, Erlang. Since changing operators af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…We plan to apply the setting to some other applications, by using the same or other deductive and inductive engines, including rules dealing with numerical or continuous features, such as time or space, and other notions of non-crisp coverage and example certainty, such as probabilities, degrees of truth, fuzzy rules, and so on. We will also keep on with the integration into our declarative learning system 5 (Martínez-Plumed, Ferri, Hernàndez-Orallo, & Ramírez-Quintana, 2013). Furthermore, other cognitive or AI systems, such as decision support systems, can benefit from the application of the metrics introduced here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We plan to apply the setting to some other applications, by using the same or other deductive and inductive engines, including rules dealing with numerical or continuous features, such as time or space, and other notions of non-crisp coverage and example certainty, such as probabilities, degrees of truth, fuzzy rules, and so on. We will also keep on with the integration into our declarative learning system 5 (Martínez-Plumed, Ferri, Hernàndez-Orallo, & Ramírez-Quintana, 2013). Furthermore, other cognitive or AI systems, such as decision support systems, can benefit from the application of the metrics introduced here.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a new learning system for knowledge acquisition that is meant to be cumulative is not an easy task. In fact, this research started while developing our system (Martínez-Plumed, Ferri, Hernández-Orallo, & Ramírez-Quintana, 2013, 2014). We were looking for a proper foundation for detailed knowledge assessment metrics and criteria for forgetting.…”
Section: Introductionmentioning
confidence: 99%
“…declarative learning system (gErl) [1,2,3,4] that meets several desirable characteristics in terms of expressiveness, comprehensibility and versatility. We have shown that more general systems can be constructed by not only giving power to data and background knowledge representation but also to a flexible operator redefinition and the reuse of heuristics across problems and systems.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Firstly we present a general-purpose There are two internal repositories containing rules and programs which are updated at each learning step by the Rule Generator and the Program Generator processes. The Reinforcement Learning Module is in charge of defining combinations of states and actions (operator applied over a rule) which will be used by the Rule Generator process to select future actions to perform.declarative learning system (gErl) [1,2,3,4] that meets several desirable characteristics in terms of expressiveness, comprehensibility and versatility. We have shown that more general systems can be constructed by not only giving power to data and background knowledge representation but also to a flexible operator redefinition and the reuse of heuristics across problems and systems.…”
mentioning
confidence: 99%
“…One of our design considerations is that the approach should work with any inductive engine that is able to generate rules, such as association rule algorithms, IP systems such as gErl [5], or ILP systems such as Progol [6]. Actually, we must also provide a deductive engine for the representation language.…”
Section: Approachmentioning
confidence: 99%